Awareness and perception on sexual and reproductive health and self-reported premarital sex among never married youth in Chaungzone township, Mon State, Myanmar (2018) - Lat, Tun W.; Aung, Yan; Thu, Min; Tun, Thandar; Mya, Kyaw S. (International Journal Of Community Medicine And Public Health, 2020)
Background: Premarital sexual practices among youth and adolescents have been highly recognized and are increasing worldwide. This study aimed to assess the awareness and perception on sexual and reproductive health and self-reported premarital sex among never married youth. Methods: The study used mixed method approach among 404 youth of equal number of male and female youth from urban and rural community using guided self-administered questionnaire and in-depth interview among 12 youth and key informant interview among 6 health professionals. Results: The study found that 11.4% (95% CI: 8.3, 14.5) of youth had premarital sex practice. After adjusting the covariates, the odds of practicing premarital sex were higher among 18 years and above (AOR=3.5, 95% CI: 1.2, 9.6), low education (AOR=3.3, 95% CI: 1.1, 10.7), youth having relationship (AOR=8.0, 95% CI: 3.0, 21.2) and youth who accepted premarital sex practice (AOR=10.9, 95% CI: 3.6, 33,1), having friends who had experience in premarital sex (AOR=3.9, 95% CI: 1.3, 11.4), compared to their counterparts. The qualitative findings revealed that most of youth and service providers did not accept premarital sex among youth because of its contradiction to traditional norms. Health care providers and youth suggested that privacy was the most critical thing in accessibility of reproductive health services among youth. All levels of providers pointed out that there were insufficient resources for provision of effective reproductive health services. Conclusions: Youth-friendly reproductive health services should be implemented to prevent unwanted pregnancy, abortions and sexually transmitted diseases to ensure safer sex practices among youth.